Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Differential advances in budburst timing among black spruce, white spruce and balsam fir across Canada - Diego S. Podadera; Lorena Balducci; Sergio Rossi; Fabrizio Cartenì; Valérie Néron; Rémi Saint-Amant; Stefano Mazzoleni; Jacques Régnière; Eric R.D. Moise; Joseph J. Bowden; Jean-Noël Candau; Alain Dupont; et al. (Agricultural and Forest Meteorology, 2024)

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Relationships of West Greenland supraglacial melt‐lakes with local climate and regional atmospheric circulation - Nathan A. Rowley; Andrew M. Carleton; John Fegyveresi (International Journal of Climatology, 2020)
Along the west‐central Greenland ice sheet (GrIS) ablation zone, the time of annual maximum occurrence of surface melt‐lakes, or peak lake period (PLP) averages June 18–July 3. This study combines atmospheric reanalysis and automatic weather station data from the Greenland Climate Network to assess the roles of synoptic circulation patterns and local climate variables, respectively, in the total melt‐lake area and count in the Sermeq Kujalleq ablation region (SKAR) for the PLPs of 2000–2016. Melt‐lake information is obtained from analysis of Landsat‐7 images. Two surface climate parameters (e.g., temperature, incoming shortwave radiation) having a strong combined effect on melt‐lake area in the SKAR are the June mean temperature, and May mean incoming solar radiation ( r = .96). Incorporating the May insolation into a regression equation permits predictability of total melt‐lake area for the study area into late June. June months classified as high melt correlate regionally with mid‐tropospheric ridging, warm air advection, and reduced cloud cover, while low melt June months are associated with a trough, cold advection, and greater cloud amount. A localized feature that we found to be prevalent during the high‐melt years are piteraq , or downsloping winds, which provide additional warming to the SKAR from adiabatic compression. Atmospheric circulation indices comprising the North Atlantic Oscillation index (NAOI) teleconnection and Greenland blocking index (GBI) pattern augment the reanalysis gridded data. We find statistically significant correlations of the NAOI and GBI with melt‐lake area ( r = −.62 and r = .77, respectively). The correlations with melt‐lake count however, are not significant; greater combined lake area and count tend to accompany the meridional mode of high amplitude Rossby waves and/or anti‐cyclonic blocking in the Greenland sector. Determining the local and synoptic‐scale atmospheric controls on supraglacial lake variability helps clarify the role of climate in the surface hydrology of the GrIS.

Small-scale spatial variation in the elemental composition of otoliths of Stegastes nigricans (Pomacentridae) in French Polynesia - Alain Lo-Yat; Mark Meekan; Niels Munksgaard; David Parry; Serge Planes; Marten Wolter; John Carleton (Coral Reefs, 2005)

Antarctic climate change during the last 50 years - John Turner; Steve R. Colwell; Gareth J. Marshall; Tom A. Lachlan-Cope; Andrew M. Carleton; Phil D. Jones; Victor Lagun; Phil A. Reid; Svetlana Iagovkina (International Journal of Climatology, 2005)

Regional-scale drought increases potential soil fertility in semiarid grasslands - Carleton S. White; Douglas I. Moore; John A. Craig (Biology and Fertility of Soils, 2004)

Directional Swimming of Fish Larvae Determines Connectivity of Fish Populations on the Great Barrier Reef - Eric Wolanski; Peter Doherty; John Carleton (The Science of Nature, 1997)